SECONDARY SCHOOL AND UNIVERSITY STUDENTS’ INTEREST IN SCIENCE SUBJECTS IN CONNECTION TO THE CHOICE OF PROFESSION - Porozovs, Juris; Dudkina, Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
One of the most important factors influencing the welfare of the society is the development of science and technology, which in turn depends on scientists and students' science literacy. The aim of the study was to investigate the interest of high school and university students in science subjects, their views on factors that raise interest in subjects and play a determining role in the choice of profession. The questionnaire of Riga secondary school and university students about their interest in science subjects in connection to the choice of their profession was carried out.  The results of the survey showed that the majority of university students are interested, or they have moderate interest about science subjects. Doctors’ assistant speciality students are more interested in science subjects in comparison with pedagogical specialities students. High school students’ interest in science subjects differs to a greater extent in comparison with university students. High school students consider the opportunity to make a career and earn good money as the most important factor in choosing a profession, pedagogical specialties students - a willingness to work in the chosen profession and an opportunity to find a job in the chosen profession, but doctors’ assistant speciality students - an opportunity to work for the community and to help people.